A review of five years’ experience on the effect of fibers on the autogenous healing of Ultra High-Performance Fiber-Reinforced Concrete - M. Roig-Flores; H. Doostkami; P. Serna (Materiales de Construccion)
Ultra High-Performance Fiber Reinforced Concrete (UHPFRC) is known for its enhanced self-healing abilities, attributed to its low water-to-cement ratio, high content of un-hydrated cement particles, and multi-cracking pattern. This study investigates the effect of different fiber types and contents on UHPFRC self-healing. Two UHPFRC mixes were evaluated: one with 65/35 3D steel fibers in a dosage of 40 kg/m³ and another with short straight-shaped steel fibers (13/0.2) in a dosage of 160 kg/m³. The self-healing performance was evaluated through crack closure and water permeability. In addition, resistance to chloride penetration was evaluated in healed cracks. Pre-cracked disk specimens with cracks between 100-450 μm were subjected to two healing conditions: water immersion at 20°C and exposure to a humidity chamber (20°C, 95% RH). The mix with higher fiber content (U160) obtained superior crack closure and healing efficiency, particularly under water immersion. For cracks smaller than 150 μm, U160 achieved nearly complete healing, while U40 achieved limited healing efficiency. In addition, water permeability and chloride penetration tests revealed that the U160 mix offered higher resistance to water and chloride penetration, emphasizing the role of fiber content and crack pattern in improving the self-healing and durability of UHPFRC.